A Comparative Study on Electrochemical Performance of GC/MFe2O4 (M = Cu & Ni)Electrodes for Oxygen Evolution (Indian Journal of Chemistry (IJC), 2025)
The ovalbumin sol-gel method manufactured the nano-sized spinel oxides Fe3O4, NiFe2O4, and CuFe2O4 at 550°C. These materials were then characterized using the physicochemical Infrared (IR) spectrophotometry method with the (XRD) and electrochemical methods (CV), and Tafel polarisation. The IR and XRD were used to establish the production of a stable spinel phase of metal oxides. IR spectra exhibited distinctive absorption bands at ~450 and ~586 cm-1 respective to the vibrations in octahedral and tetrahedral voids in spinel oxides. The development of nano-sized oxides with crystallite diameters of 28, 11, and 45 nm for pure, Ni, and Cu-ferrites was verified by XRD powder patterns of decomposed oxide. The electrocatalytic performance for the oxygen evolution process was investigated using the CV and Tafel polarization techniques. in an alkaline medium on a fabricated GC/oxides/1MKOH electrode interface. Tafel slopes for (OER) at the higher over-potentials region ranged between (b= 118 -140 mV dec-1) and followed almost first-order reaction mechanism and thermodynamic parameters such as the electrochemical activation energy () at constant potentials (0.84V) and the electrochemical entropy (for OER were also estimated from the Arrhenius plot, with observed values ranging from 6 to 39 kJ mol-1 and a highly negative value of entropy () = -330 J deg-1 mol-1), respectively.